2019
DOI: 10.18632/aging.102407
|View full text |Cite
|
Sign up to set email alerts
|

A cluster of long non-coding RNAs exhibit diagnostic and prognostic values in renal cell carcinoma

Abstract: Kidney cancer ranked in the top 10 for both men and women in the estimated numbers of new cancer cases in the United States in 2018. Targeted therapies have recently been administered to patients with clear cell renal cell carcinoma (ccRCC), but the overall survival of patients at the terminal stage of the disease has not been as good as expected. It is therefore necessary to uncover efficient biomarkers for early diagnosis, and to clarify the molecular mechanisms underlying ccRCC progression and metastasis. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 84 publications
2
29
0
Order By: Relevance
“…Globally, RCC accounts for more than 2% of neoplasms in humans worldwide with the incidence and mortality persistently increasing 1 . Recently, gene signatures based on specific characteristic-related to predict prognosis have become a hotspot in cancer research 13 15 . In the present study, to the best of our knowledge, we constructed the first novel metabolism-related risk signature with the potential application of predicting the prognosis and progression of ccRCC.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, RCC accounts for more than 2% of neoplasms in humans worldwide with the incidence and mortality persistently increasing 1 . Recently, gene signatures based on specific characteristic-related to predict prognosis have become a hotspot in cancer research 13 15 . In the present study, to the best of our knowledge, we constructed the first novel metabolism-related risk signature with the potential application of predicting the prognosis and progression of ccRCC.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, IGFL2-AS1 was found to be involved in breast cancer progression. 17 In renal cell carcinoma, Cheng et al 18 identified IGFL2-AS1 as a diagnostic and prognostic marker. However, the functional role of IGFL2-AS1 has not been studied in GC.…”
Section: Introductionmentioning
confidence: 99%
“…There are more than 1.8 million new cancer cases in the USA alone in 2020, and around 4% of which are estimated to be kidney or renal pelvis tumors (1). Renal cell carcinoma (RCC) is the most common solid tumor of the adult kidney, accounting for 87% of all renal malignant tumors (2). Curative intervention via surgical resection (either partial or radical nephrectomy) has been the primary standard treatment for individuals with clinically localized RCC (3).…”
Section: Introductionmentioning
confidence: 99%